Decentralized Communication Patterns and Solidarity in Indonesian Football Supporter Groups - Pembayun, Jaduk Gilang; Yusliwidaka, Arnanda; Rhizky, Deani Prionazvi; Rihardi, Satrio Ageng; Hutama, Ryan Pambudi (LifeSciFi, 2025)
This study examines the comprehensive communication patterns and forms of support within Brigata Curva Sud (BCS), the supporter group of PSS Sleman, which is known for its strong solidarity, creativity, and collective coordination. Unlike other football supporter organizations in Indonesia that adopt hierarchical leadership structures, BCS operates through a decentralized and participatory model where decisions are made collectively in forums. The research aims to explain and describe the communication patterns within the Brigata Curva Sud PSS Sleman supporter group in supporting PSS Sleman. Using a qualitative descriptive method with observation, interview, and documentation techniques, this study applies the concept of all-channel communication to analyze the interaction among members. The findings reveal that BCS’s communication pattern allows open participation among members, fostering innovation in various support activities such as 90-minute chants, visual choreography, and economic initiatives through Curva Sud Shop (CSS). These practices not only sustain the group’s identity but also strengthen the economic base of the club. The study implies that a non-hierarchical communication structure can enhance collective creativity, unity, and social impact within fan communities, serving as a model for other supporter organizations and community-based movements in Indonesia.